BS ENISO 10360-11. Geometrical product specifications (GPS). Acceptance and reverification tests for coordinate measuring systems (CMS). Part 11. CMSs using the principle of X-ray computed tomography (CT) (8th April 2021) - British Standards Institution,
No abstract available